Chemical Probes in Biology: Science at the Interface of Chemistry, Biology and Medicine - Schneider, Manfred P. (NATO science series, 2003)
The field of Bio-organic Chemistry or Chemical Biology, as it it also called, constitutes a highly interdisciplinary branch of chemistry, beyond the traditional pathways in which chemists and biologists have been working in the past. The topics covered in this book include inter alia: anticancer agents, antioxidants, chemotaxis, carbohydrates, DNA detection and delivery, enzyme structure, enzyme assisted syntheses, fluorescent probes, gene therapy, genomics, inositol phospholipids, inositol phosphates, multivalent ligands, organic syntheses, oxidative stress, photoaffinity labeling techniques, natural products - syntheses and biological activities, phospholipases, proteomics, receptors such as tyrosine kinases, signal transduction phenomena, x-ray crystallography and many more. The book represents an excellent survey of the current stete of the art in an exciting area of interdisciplinary science and supplies an incentive for increased cooperation in Science at the Interface of Chemistry, Biology and Medicine